PENGARUH MODUL TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PRAKTEK KADER DALAM UPAYA PEMBERIAN ASI EKSKLUSIF - Jumiyati, nFN; A, Nugrahaeni S; Margawati, Ani (PERSATUAN AHLI GIZI INDONESIA, 2014)
Rendahnya cakupan ASI eksklusif dipengaruhi oleh terbatasnya tenaga konselor ASI, belum maksimalnya kegiatan edukasi, sosialisasi dan belum optimalnya membina kelompok pendukung ASI. Kelompok pendukung ASI di masyarakat dapat melibatkan peran kader dengan cara menambah pengetahuan, sikap dan praktek kader. Penelitian bertujuan untuk menganalisis pengaruh modul terhadap peningkatan pengetahuan, sikap dan praktek kader dalam upaya pemberian ASI eksklusif. Desain quasi experimen dengan rancangan non randomized control group pre test – post test design. Sampel penelitian 60 kader (30 kelompok perlakuan dan 30 kontrol). Perilaku kader diukur 4 kali yaitu pada kondisi awal, setelah pelatihan, satu bulan, dan dua bulan setelah pelatihan. Dilakukan uji beda rata-rata. Kelompok perlakuan terjadi peningkatan skor pengetahuan 9,63 poin, post-test bulan pertama 8,94 poin dan post-test bulan kedua 1,55; sikap meningkat 6,35 poin, post tes bulan pertama 7,5 poin dan post-test bulan kedua tidak terjadi peningkatan; praktek meningkat 4,55 poin, post-test bulan pertama 11,8 poin dan post-test bulan kedua 0,39 poin. Kelompok kontrol terjadi peningkatan pengetahuan 3,25 poin, sikap meningkat 2,03 poin dan praktek meningkat 2 poin. Pelatihan dengan menggunakan modul dapat meningkatkan pengetahuan, sikap dan praktek kader dibandingkan kelompok kontrol.ABSTRACT THE IMPACT OF MODULE INCREASE KNOWLEDGE, ATTITUDE AND PRACTICE AMONG THE HEALTH SERVICE PROVIDERS TO PROMOTE EXCLUSIVE BREASTFEEDING The low coverage of exclusive breastfeeding is influenced by limited of breastfeeding counselor, educational activities, socialization and lack of involving breastfeeding support groups. Support groups in the community can involve health service provider participation in improving knowledge, attitude and their practice. The Objective of this study is to analyze impact of the module toward increase the knowledge, attitude and practice of health service providers to promote the breastfeeding. The desain of the study research design used a quasi experiment with the design of non-randomized control group pre test-post test design. The sample was 60 health service providers (30 as treatment group and 30 as control group). Health service providers behavior was measured 4 times on the initial conditions, after training, one month, and two months after training used different test average. The result shows that there was an increase in treatment group by 9.63 points, the first month post-test by 8.94 points and at the second post-test by 1.55, for attitude increased 6.35 points, the first month post-test by 7,5 points and at the second month test showed no improvment, the practice increased by 4.55 points, the first month post-test by 11.8 points and second month post-test by 0.39 points. In control group, there was an increase of knowledge by 3.25 points, for attitude increased by 2,03 points and practice increased by 2 point. Training using the module can improve knowledge, attitude and practice of health service providers compared to those without the control group.Keywords: training module, knowledge, attitude and practice of health service providers, exclusive breastfeeding